2022-RA-1406-ESGO A review of ovarian cancer in Northern Ireland: a retrospective cohort study. (20th October 2022) - McMullan, Josh Courtney; Rannaghan, Lisa; Harley, Ian; Dobbs, Stephen; McComiskey, Mark; Craig, Elaine; Nagar, Hans
Abstract : Introduction/Background: In Northern Ireland (NI) an average of 211 women are diagnosed with ovarian cancer each year with a median age at diagnosis of 65. Ovarian cancer is not a single disease but is comprised of distinct subtypes with a considerable variation in outcomes. In 2018 a funded ovarian cancer feasibility pilot was commenced in England with the aim to extend to all four UK nations. Methodology: All patients diagnosed with epithelial ovarian, fallopian tube and primary peritoneal cancer in NI were included between 2014 and 2017. Patients with non-invasive epithelial (borderline) tumours were excluded. Data was collected using electronic data sources. Observed 5-year survival and time to disease recurrence was estimated by Kaplan Meier method. Results: 603 patients in total with two thirds of women present with advanced (stage 3/4) disease. High grade serous carcinoma (HGSC) was the most common subtype (69%). 11% were palliative and two thirds developed recurrence. Low grade serous, mucinous and endometrioid 5 year survival was 81%, 80% and 70% respectively compared to 49% for clear cell and 21% for HGSC.Specifically for HGSC 42% had cytoreduction with chemotherapy (48% complete, 35% optimum), 16% were deemed unfit for active treatment. Median time to progression was 29 months for primary surgery and 16 months for interval surgery. Median overall survival was 24 months (primary cytoreduction 58 months and interval cytoreduction 37 months). Conclusion: The outcomes for patients vary significantly based on the histological subtype at diagnosis. HGSC remains the most common subtype with a 5 year survival of 21%.